Identity of some recently described Lepidoptera from France—re-assessed with DNA barcodes and morphology - Huemer, Peter; van Nieukerken, Erik J. (Zootaxa, 2021)
Seventy-three species of Lepidoptera described from France since 2000, particularly by Jacques Nel and Thierry Varenne, are re-assessed from largely unpublished molecular data. We tried to obtain DNA barcode sequences from 62 holotypes, supplemented by paratypes of eight species and on one case by non-type material, whereas one previously synonymized species was not sequenced. Altogether we obtained 78 DNA barcode sequences for 65 nominal taxa while sequencing failed for six holotypes. An integrative analysis from molecular data and morphology supports the validity of the majority of species but also resulted in the re-assessment of several taxa. The following 13 new synonymies are established: Stigmella cyrneorolandi Nel & Varenne, 2013 syn. nov. of Stigmella rolandi van Nieukerken, 1990; Stigmella thibaulti Varenne & Nel, 2019 syn. nov. of Stigmella nivenburgensis (Preissecker, 1942) (Nepticulidae); Nemapogon peslieri Varenne & Nel, 2017 syn. nov. of Nemapogon inexpectata Varenne & Nel, 2017 (Tineidae); Phyllonorycter acericorsica Varenne & Nel, 2015 syn. nov. of Phyllonorycter ochreojunctella (Klimesch, 1942) (Gracillariidae); Ancylis paraobtusana Varenne, Nel, & Peslier, 2020 syn. nov. of Ancylis comptana (Frölich, 1828) (Tortricidae); Celypha paludicolella Varenne & Nel, 2017 syn. nov. of Celypha doubledayana (Barrett, 1872) (Tortricidae); Cydia oxytropidana Nel & Varenne, 2016 syn. nov. of Cydia oxytropidis (Martini, 1912) (Tortricidae); Sorhagenia orocorsa Varenne & Nel, 2016 syn. nov. of Sorhagenia janiszewskae Riedl, 1962 (Cosmopterigidae); Chionodes cerdanica Peslier, Nel & Varenne, 2020 syn. nov. of Chionodes distinctella (Zeller, 1839) (Gelechiidae); Elachista bidentata Varenne & Nel, 2019 syn. nov. of Elachista orstadii Palm, 1943; Elachista karsticola Varenne & Nel, 2018 syn. nov. of Elachista maculosella Chrétien, 1896 (Elachistidae); Scythris chablaisensis Delmas, 2018 syn. nov. of Scythris laminella ([Denis & Schiffermüller], 1775) (Scythrididae); Epermenia pumila (Buvat & Nel, 2000) syn. nov. of Epermenia profugella (Stainton, 1856) (Epermeniidae). Finally, the status of some taxa still remains unclear due to the lack of DNA barcodes of closely related species and the absence of convincing diagnostic characters in morphology.